Dynamic Valuation Modelling of Cost and Electricity Consumption Over Local Objects with Intellectual Governance - Osypenko, V.V.; Kaplun, V.V.; Voronenko, M.O. (Control systems & computers, 2020)
The work is devoted to the further development of the theory of intelligent electric power management systems construction for local objects with several heterogeneous (traditional and renewable) energy sources. The scientific idea is based on the use of modern information systems and technologies and is to improve the energy efficiency of the micro-energy networks of local objects based on the dynamic estimation of the real-time electricity cost and the transmission of this information to the user with the agreed discretion for matching the load schedule (or demand schedule). The method of dynamic planning of energy use in micro-energy systems and principles of building intelligent energy management systems of local objects are developed, on the basis of which the user will be able to control the load levels in real-time and optimize the energy costs, which in turn will lead to balancing of the microelectric network and increase the efficiency of its functioning. It is proved that the proposed solutions for the formation of control and technological functions can be used to improve the intelligent control systems in technologies smart microgrid, smart house, etc. Мета статті. Метою дослідження є розробка методу децентралізованого динамічного планування використання енергоресурсів та обґрунтування принципів побудови інтелектуальних систем управління енергоспоживанням локальних об’єктів шляхом оптимального узгодження між попитом (графіками електроспоживання) та динамічно змінюваною вартістю електроенергії у реальному часі для підвищення енергоефективності мікроенергетичних систем. Методи. Системний підхід, системний аналіз, індуктивні технології моделювання, енергетичний менеджмент. Результати. Розроблено метод децентралізованого динамічного планування використання енергоресурсів в мікроенергетичних системах і основні принципи побудови інтелектуальних систем управління енергоспоживанням локальних об'єктів, на основі яких користувач зможе контролювати рівень навантаження в реальному часі і оптимізувати витрати на електроенергію, що в свою чергу призведе до балансування мережі і підвищить енергоефективність її функціонування. Цель статьи. Целью исследования является разработка метода децентрализованного динамического планирования использования энергоресурсов и обоснование принципов построения интеллектуальных систем управления энергопотреблением локальных объектов путем оптимального согласования между спросом (графиками электропотребления) и динамично меняющейся стоимостью электроэнергии в реальном времени для повышения энергоэффективности микроэнергетических систем. Методы. Системный подход, системный анализ, индуктивные технологии моделирования, энергетический менеджмент. Результаты. Разработан метод децентрализованного динамического планирования использования энергоресурсов в микроэнергетичних системах и основные принципы построения интеллектуальных систем управления энергопотреблением локальных объектов, на основе которых пользователь сможет контролировать уровень нагрузки в реальном времени и оптимизировать затраты на электроэнергию, что в свою очередь приведет к балансированию сети и повысит энергоэффективность ее функционирования.